KENDALA GURU DALAM INTERNALISASI NILAI KARAKTER PADA PEMBELAJARAN SEJARAH - Tsabit Azinar Ahmad (Khazanah Pendidikan, 2014)
This research describes character educational values and their constraints in internalize it on learning history at senior high school. Interview and document studies were used to collect information. Interactive model of data analyze were chosen in this research consist of several stages, i.e. data reduction, data display, and conclusion. Result of study shown internalization of character values are necessity. It caused learning history potentially become a media for values transmission through historical event and exemplary of heroes. Nevertheless, there was several constaints in internalization of character values. It appears in teachers' understanding, students’ attitude, learning practice, and school culture does not support character education optimally. For that, there need sustainable effort, teachers’ creativity to instill character and exemplary in learning process in order to achieve internalization of values work optimally. Keywords: teachers’ constaints, character education, learning history